ECOLOGICAL, TECHNICAL AND ECONOMICAL PERFORMANCE INHANCEMENT IN DIESELS AS A RESULT OF ADDITIONAL AIR SUPPLY OF THE CYLINDERS - Пушка, О. С.; Войтік, А. В.; Назаренко, О. О.; Кутковецька, Т. О. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The issues of improving the transition processes in turbocharging diesel engines, strengthening fuel and economic performance, as well as reducing smoke content in exhaust gases due to additional air supply of diesel cylinders, are up-to-date. One of the ways to improve the performance of diesel engines is the use supercharger gas turbine with a short-term supply of compressed air from bombs to diesel cylinders. The research is based on the development of an automatic regulation system for the additional air supply of automotive diesel engines cylinders in terms of optical density of exhaust gases. Additional air supply reduces the time of the transition process, improves environmental, dynamic, fuel and economic indicators. The developed automatic control system provides adjustment of air supply at a given value of the maximum acceptability of smoke content in exhaust gases within all modes of the diesel engine operation. The study demonstrated that there is cutting time of about 0.2 seconds in the transition process, the value of smoking content in exhaust gases is reduced at 31%, and the mass soot emission is reduced at 51%. The results of the study suggest that more efficient work of the engine is accompanied by a decrease of powerful fuel burn at 6-8%